Use of a novel antigen expressing system to study the Salmonella enterica serovar Typhi protein recognition by T cells - Salerno-Gonçalves, Rosângela; Tettelin, Hervé; Lou, David; Steiner, Stephanie; Rezwanul, Tasmia; Guo, Qin; Picking, William D.; Nene, Vishvanath M.; Sztein, Marcelo B. (Public Library of Science, 2017)
Salmonella enterica serovar Typhi (S. Typhi), the causative agent of the typhoid fever, is a pathogen of great public health importance. Typhoid vaccines have the potential to be cost-effective measures towards combating this disease, yet the antigens triggering host protective immune responses are largely unknown. Given the key role of cellular-mediated immunity in S. Typhi protection, it is crucial to identify S. Typhi proteins involved in T-cell responses. Here, cells from individuals immunized with Ty21a typhoid vaccine were collected before and after immunization and used as effectors. We also used an innovative antigen expressing system based on the infection of B-cells with recombinant Escherichia coli (E. coli) expressing one of four S. Typhi gene products (i.e., SifA, OmpC, FliC, GroEL) as targets. Using flow cytometry, we found that the pattern of response to specific S. Typhi proteins was variable. Some individuals responded to all four proteins while others responded to only one or two proteins. We next evaluated whether T-cells responding to recombinant E. coli also possess the ability to respond to purified proteins. We observed that CD4+ cell responses, but not CD8+ cell responses, to recombinant E. coli were significantly associated with the responses to purified proteins. Thus, our results demonstrate the feasibility of using an E. coli expressing system to uncover the antigen specificity of T-cells and highlight its applicability to vaccine studies. These results also emphasize the importance of selecting the stimuli appropriately when evaluating CD4+ and CD8+ cell responses.